THE INFLUENCE OF INTERNET TECHNOLOGY ON THE DEVELOPMENT OF TEACHING AND LEARNING METHODS FOR STUDENTS - Alvin Rizky Pratama; Mita Yulianti Taufik; Acep Haryudin (PROJECT (Professional Journal of English Education), 2019)
The research titled the Influence of Internet Technology on The Development of Teaching  And Learning Methods For Students is aimed to easier learning process at the class with studets. Information and communication technology are fenomenal and the beginning of the emergence of a web application is the internet. Internet which originated from research to defense and security as well as educational support tolls business evolved into a very influential. This is also encouraging to provide internet service facility. Students who have signed up to can do anything, including transaction log, learn, etc. with the technology services can solve the problems facing employes who leave in especially for those who work while studying or courses. Internet is very important to considered the problem learning and teaching. The purpose of the study is intended to obtain data and information on the effect to the use internet and browser for educational programs. The results of this study found that the role of information technology an education, in addition to helping students in learning also had a quite influentialrole for teachers, especially in the use of facilities to end rich teaching skills and guidance for the development of science and technology n order to strengthen in iprove human well – being.